University objectives and socio-economic results regarding engineering: multi-criteria measuring of alignment (2011)
University faculties and schools develop mechanisms for knowledge transfer as tools for achieving goals stated in a university’s mission regarding its socio-economic environment. The main purpose of this paper is to present the results obtained after measuring the degree of alignment of a university’s strategic objectives with results obtained by a faculty through its knowledge transfer mechanisms. This allows for diagnosis by comparing the situation desired by the university management team (expected case) with actual results achieved by developing plans applying the knowledge transfer mechanisms (real case). Multi-criteria decision analysis techniques (MCDA) were thus applied, namely analytic network process (ANP) and analytic hierarchy process (AHP). The results relied on the experience and perceptions of the experts who participated in the study. The methodology proposed in this paper has been applied in the Universidad Nacional de Colombia’s Faculty of Engineering. The study led to measuring the importance of each of a university’s strategic objectives, the results achieved in a faculty regarding each objective, the degree of alignment between expected and actual results and each knowledge transfer mechanism’s level of influence.